PENDAMPINGAN IMPLEMENTASI TEKNOLOGI DIGITAL INFORMASI PEMAKAMAN BERBASIS CLOUD UNTUK MENINGKATKAN LAYANAN ADMINISTRASI PADA FKPM - Kurniawan, Helmi; Tanjung, Yahya; Hardianto, Hardianto; Rahmadi, Diky; Farhan, Muhammad (LPPM Universitas Nusa Mandiri, 2025)
The Forum Komunikasi Pengembangan Makla (FKPM) is a cemetery management body that faces challenges in managing data from the Serikat Tolong Menolong (STM) and cemetery information services. The main problem lies in the limitations in delivering information and the slow adoption of information technology in the administration system. To overcome this, the Pengabdian kepada Masyarakat Team (PKM) of the Potensi Utama University implemented the Pemberdayaan Berbasis Masyarakat (PBM) program through a participatory approach in three stages: socialization, training (workshops), and structured mentoring. All of these stages support the implementation of cloud-based digital information technology to improve service quality and data management efficiently. The implementation method includes needs analysis through site visits and interviews, design and development of web-based applications, system usage training, application trials, and periodic monitoring and evaluation. This activity also involves students in the Merdeka Belajar-Kampus Merdeka (MBKM) scheme through internship programs relevant to information technology courses. The results of the program showed an increase in the knowledge of FKPM administrators by 96.17% and an increase in digital data management skills of up to 92.86%. The implementation of the cloud system accelerates the previously manual administrative process to be faster, more accurate, and more efficient, as well as increasing the openness of information to the public. This program has been published through accredited national journals and electronic media, and is expected to be a pilot model for the application of digital technology in similar public services in other regions.